2005
DOI: 10.1152/ajpheart.00674.2004
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical attenuation of leukocyte rolling in response to ischemia- reperfusion and extracorporeal blood circulation in inflamed tissue

Abstract: In contrast to acute preparations such as the exteriorized mesentery or the cremaster muscle, chronically instrumented chamber models allow one to study the microcirculation under "physiological" conditions, i.e., in the absence of trauma-induced leukocyte rolling along the venular endothelium. To underscore the importance of studying the naive microcirculation, we implanted titanium dorsal skinfold chambers in hamsters and used intravital fluorescence microscopy to study venular leukocyte rolling in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(87 reference statements)
0
6
0
1
Order By: Relevance
“…Although multiple mediators work together in inflammation, LTB 4 has been implicated in the initiation of leukocyte-endothelium interaction during inflammation (Schafer et al, 2005). In our study, the enhanced LTB4-induced leukocyte adhesion observed in hypertensive rats was attenuated by castration, which suggests that endogenous testosterone exerts a proinflammatory effect contributing not only for the increased leukocyte rolling but also for the increase in leukocyte adherence in SHRs.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Although multiple mediators work together in inflammation, LTB 4 has been implicated in the initiation of leukocyte-endothelium interaction during inflammation (Schafer et al, 2005). In our study, the enhanced LTB4-induced leukocyte adhesion observed in hypertensive rats was attenuated by castration, which suggests that endogenous testosterone exerts a proinflammatory effect contributing not only for the increased leukocyte rolling but also for the increase in leukocyte adherence in SHRs.…”
Section: Discussionmentioning
confidence: 45%
“…Leukocytes adhering to the endothelium were quantified following the superfusion of the irritant stimulus leukotriene B 4 (LTB 4 20 nM, Cayman Chemical CO, EUA) for 10 min (Schafer et al, 2005). A leukocyte was considered to be adherent to the venular endothelium if it remained stationary for more than 30 s along 100-μm length of venule.…”
Section: Leukotriene B 4 -Induced Leukocyte Adhesion and Transmigrationmentioning
confidence: 99%
“…This number compares well to experiences made in other immunocompetent mouse species (C57BL/6, BALB/c, and ApoE KO, all showing an elimination rate of around 40%, see Li and Förstermann, 2000;Schaefer et al, 2005), but was slightly higher when compared to mice that are genetically hairless (nu/nu or nude, showing an elimination rate of around 25%; see Lehr et al, 1993). It should be acknowledged that the success rate of the chamber preparation depends largely on the quality of microsurgical technique and hence varies from experimentor to experimentor (unpublished observation), and that unexpected results are obtained in experiments in which the above described strict criteria are neglected (Schäfer et al, 2005). To eliminate the effects of anesthesia and direct surgical trauma on the microvasculature, a recovery period of 72-96 h was allowed between the implantation of the observation chambers and the intravital microscopic investigations.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were counted for 30 seconds and normalized by cross‐section circumference of each microvessel. Sticking was defined as stable binding at a certain position for more than a 30 seconds period, expressed as the number of cells per endothelial surface (as calculated from the microvessel diameter and the defined length of 200 µm) 11. At least 3 different vessels were analyzed per animal, and measurements were performed before PDT, 90 and 180 minutes after PDT.…”
Section: Methodsmentioning
confidence: 99%